Temporal dynamics and spatial patterns of drought and the relation to ENSO: a case study in Northwest China - Liu, Zhiyong; Menzel, Lucas; Dong, Chunyu; Fang, Ruihong (International journal of climatology, 2016)
An investigation of temporal dynamics and spatial patterns of dryness/wetness conditions over the eastern part of Northwest China (including Shaanxi, Ningxia, the eastern part of Gansu, and a part of southern Inner Mongolia) during the period 1960-2009 is presented. The analysis of this study is threefold. First, the dryness/wetness conditions over the study area were characterized using the self-calibrating Palmer Drought Severity Index (PDSI). The spatiotemporal variability of dryness/wetness conditions in the study area was then investigated by the rotated empirical orthogonal function (REOF) and Mann-Kendall trend test. Third, we examined the periodical oscillations of dryness/wetness conditions and the multi-scale relationships between dryness/wetness conditions and El Niño-Southern Oscillation (ENSO). The results indicate that most parts of the study area were characterized by a dry trend in both the rainy season (May-September) and winter. Four sub-regions of dryness/wetness conditions across the study area were identified. Based on the wavelet analysis, the periodical features in the PDSI time series for each sub-region were explored. Negative relationships between the PDSI in the sub-region I (representing the central and southern parts of Shaanxi and the southeastern Gansu) and the Niño 3.4 index can be consistently detected on 2-6 year scales during the entire period 1960-2009. This suggests that the strong El Niño events generally lead to very dry conditions in the sub-region I on multi-year scales. In addition, we further investigated how the ENSO cycle modulates the strength of the East Asian summer monsoon (EASM) in both developing and decaying phases of El Niño and La Niña events. The results of this study could be beneficial for efficient water resources management and drought assessment in the current study area and also provide a valuable reference for other areas with similar climatic characteristics.
Published online 19 October 2015
Gesehen am 28.05.2020